Diagnostic performance of Midkine ratios in fine-needle aspirates for evaluation of Cytologically indeterminate thyroid nodules - Le Zhou; Jinxi Jiang; Yantao Fu; Daqi Zhang; Tong Li; Qingfeng Fu; Chao Yan; Yifan Zhong; Gianlorenzo Dionigi; Nan Liang; Hui Sun (BMC, 2021)
Abstract Background Fine-needle aspiration cytology (FNAC) is a basic diagnostic tool for thyroid nodules. However, 15-30% of nodules are cytologically indeterminate. Midkine (MK), a pleiotropic growth factor, is often upregulated in patients with cancers. This study aimed to evaluate the role of MK and its ratios in fine-needle aspirates (FNA) for predicting thyroid malignancy. Methods This retrospective study included patients with thyroid nodules who underwent preoperative FNA and/or thyroidectomy between April 2017 and September 2017. MK levels in FNA washout were measured by enzyme-linked immunosorbent assay, and thyroglobulin (TG) and free thyroxine (FT4) levels in FNA washout were measured by chemiluminescent immunometric assays. Results A total of 217 patients with 242 nodules were included in this study. The concentrations of TG, FT4, MK/TG, MK/FT4, and FT4/MK were significantly different between papillary thyroid carcinomas and benign thyroid nodules. Both MK/TG and MK/FT4 ratios were positively correlated with maximum tumor diameter, extrathyroidal extension, and T and N stages. The area under the curve for MK/TG was 0.719 with a cutoff value of 55.57 ng/mg, while the area under the curve for MK/FT4 was 0.677 with a cutoff value of 0.11 μg/pmol. FNAC in combination with MK/FT4 had a higher sensitivity (95% vs. 91%) and accuracy (96% vs. 92%) than FNAC alone for cytologically indeterminate specimens, those of unknown significance, or those suspected of malignancy. Conclusions MK/FT4 and MK/TG may have diagnostic utility for evaluation of papillary thyroid carcinomas, particularly for cytologically indeterminate thyroid nodules.